Integrative analyses of conserved WNT clusters and their co-operative behaviour in human breast cancer - Qurrat-ul-Ain (Biomedical Informatics, 2011)
In human, WNT gene clusters are highly conserved at specie level and associated with carcinogenesis. Among them, WNT-10A and WNT-6 genes clustered in chromosome 2q35 are homologous to WNT-10B and WNT-1 located in chromosome 12q13, respectively. In an attempt to study co-regulation, the coordinated expression of these genes was monitored in human breast cancer tissues. As compared to normal tissue, both WNT-10A and WNT-10B genes exhibited lower expression while WNT-6 and WNT-1 showed increased expression in breast cancer tissues. The co-expression pattern was elaborated by detailed phylogenetic and syntenic analyses. Moreover, the intergenic and intragenic regions for these gene clusters were analyzed for studying the transcriptional regulation. In this context, adequate conserved binding sites for SOX and TCF family of transcriptional factors were observed. We propose that SOX9 and TCF4 may compete for binding at the promoters of WNT family genes thus regulating the disease phenotype.